Overcrowded housing: One of a constellation of vulnerabilities for child sexual abuse. (July 2019) - Cant, Rosemary L.; O'Donnell, Melissa; Sims, Scott; Harries, Maria
Abstract: Background: Effective prevention of child abuse depends on an understanding of factors associated with the abuse. Increased risk of child sexual abuse has been associated with parental substance use and adverse socio-economic factors such as living in poverty and parental unemployment. This study investigated overcrowding as a potential socio-economic risk factor in child sexual abuse taking into account other socio-economic, child and parental factors. Method: This study used de-identified linked data from health and child protection data collections for the cohort of children born in Western Australia from 1990 to 2009 (n = 524, 478). Cox regression was used to estimate adjusted and unadjusted hazard ratios and 95% confidence intervals for time to first sexual abuse allegation and first substantiated allegation, relative to the level of overcrowding and controlling for other risk factors. Results: Higher levels of household overcrowding were associated with a 23%–46% increase in the risk of child sexual abuse allegations. Only the highest level of overcrowding was associated with a 40% increased risk of substantiated sexual abuse. Conclusion: The findings suggest that overcrowded living conditions are associated with an increased risk of sexual abuse for some children. This factor needs to be considered alongside other risk factors when assessing and improving child safety.